About BRICS Investment Arbitration - O. Yu. Skvortsov (Евразийская интеграция: экономика, право, политика)
The article discusses the issue of creating investment arbitration in the BRICS member states. The prerequisites for the creation of this institution are the problems of “classical” investment arbitration, which, in turn, are predetermined by the crisis of globalism as an idea of the world order.Aim. The purpose of this work is to study the prerequisites and the possibility of creating investment arbitration in the BRICS countries.Tasks. Within the framework of achieving this goal, the following tasks were solved: analysis of the crisis of the idea of globalism and, as a consequence, the crisis of “classical” investment arbitration; analysis of the regionalization of legal institutions in general and investment arbitration, in particular; analysis of the conditions for the creation of investment arbitration in the BRICS member states.Methods. The methodology of solving the formulated tasks is based on the identification of those patterns that are characteristic of various periods of the existence of world political, economic and legal relations.Results. The prerequisites for the creation of BRICS investment arbitration are the problems of “classical” investment arbitration. The author concludes that this crisis entails a tendency to regionalize both communities of states and legal institutions that ensure the functioning of these unions. Hence, there is a need for the formation of regional arbitrations. Since the BRICS community has set as its goal the formation of a coordinated financial, trade and investment policy, it also required the appropriate jurisdictional support of these processes. In addition to the creation of other institutions, the economic needs of the BRICS require the creation of investment arbitration, which should become a mechanism for resolving investment disputes arising between various economic entities.Conclusions. It is concluded that when creating investment arbitration, it is necessary to abandon the ideology of protecting exclusively the rights of the investor, which has become the dominant idea in matters of economic law and order. In particular, it is necessary to take into account the interests of public entities — recipients of investments. These interests lie in the plane of protecting human rights, public needs, and environmental problems. In addition, it is necessary to abandon the exclusive use of the Anglo-Saxon legal technique, which is imposed within the framework of the existing investment arbitration. In the end, the conclusion is made about the relevance of the creation of the BRICS investment arbitration, that this institution will contribute to the strengt hening and development of ties betw een the states participating in this association.